A sala de aula invertida no ensino de biologia no ensino médio integrado à educação profissional: um estudo de caso - Cacau, Joquebede Bezerra (2020)
In High School, there is a constant complaint from Biology teachers regarding the students' lack of interest in the subject. This lack of interest is reflected in poor performance on school tests, as well as student complaints about the extensive content and with many technical terms. In this context, the information and communication technologies have been gradually inserted in the pedagogical practice, helping the transmission of content and modifying the relationship of the student with this content. The Flipped Classroom is the Blended Learning mode in which, before the class day, students get instructions about the content, through texts, video classes or any other virtual material send by the teacher. At the class, teacher proposes activities to fix and deepen the content. The present work aimed to analyze the perceptions of the students and mentor teacher about the Inverted Classroom in the Biology teaching of five classes of a State School of Professional Education High School in Fortaleza (Ceará), in 2018, and its influence on student learning. It was decided to carry out an exploratory qualitative case study research. To this end, for six months the flipped classroom methodology was applied to the project participants classes. After this period, three mentor teachers were interviewed and a questionnaire was applied with 168 students. Students' talk in conversation circles and class council meetings about the applied methodology were also analyzed, as well as the researcher's notes about her perceptions in the research diary. The study pointed out that the use of educational technologies changed the school routine, reducing paper consumption, speeding up the evaluation and grade recording processes. Students were more interested in the subject. They showed more active learning in classes and developed greater autonomy in the study routine. The main challenges for SAI during the research are the lack of good quality connectivity at school and the difficulty of adapting the methodology to a deaf-mute student. Finally, the study indicated that flipped classroom may be an alternative to make biology teaching more dynamic and enjoyable for students, contributing to more meaningful learning despite the challenges encountered.